STUDI KORELASI PERSEPSI ANAK PADA ORANG TUA SEBAGAI PENGAJAR DI RUMAH SELAMA MASA PANDEMI DENGAN PRESTASI BELAJAR - Yoseph Lidi; Muhammad Marvel Aditya; Maretha Tannia Meilly (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2023)
Children's perception of parents as democratic teachers at home during PJJ is a form of parental participation. The process of implementing PJJ is due to the Covid-19 pandemic. With the involvement of parents as teachers at home during PJJ, it encourages children to gain maximum knowledge. Thus, we propose a hypothesis that there is a relationship between children's perceptions of parents as teachers and learning achievement. The method used in this research is correlation, which is to see the form of relationship between variables, namely the relationship between children's perceptions of parents as democratic teachers and learning achievement. As for how to obtain data, the implementation of library research (Library Research) and online research. The population in this study were 17 students from SDK Santo Yusup and 17 students from SD Pembangunan Jaya 2. While the sample was a partial sample of grade 1 and grade 2 students. Data collection techniques through observation, interviews, documentation and questionnaire distribution. Data management is done by product moment analysis. The variables studied were children's perceptions of parents as teachers at home during the pandemic (X) and learning achievement (Y). The results of the study using product moment correlation analysis show that the calculation result of rxy, which is -0.251696. These results indicate that there is no correlation between the two variables. So, there is no correlation between children's perceptions of parents as teachers at home during Distance Learning (X) and learning achievement (Y), indicating the accepted hypothesis is H0.